RESERVATION OF LABOR SPOTS FOR WOMEN VICTIMS OF DOMESTIC VIOLENCE IN ADMINISTRATIVE CONTRACTS: GENERAL OR SPECIFIC RULE? AN ANALYSIS IN LIGHT OF THE RIGHTS OF VULNERABLE GROUPS. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This study seeks to investigate whether the provision set forth in Article 25, Paragraph 9, of Law No. 14,133/2021—which guarantees reserved positions for women who are victims of domestic violence in public bidding processes and contracts—has a general scope, applicable to all levels of government, or whether it is a specific provision for the federal government, limited to federal bidding. To this end, it is necessary to understand the current status of domestic violence in Brazil, especially in recent years; identify the factors that hinder women from severing abusive relationships; and, finally, determine how the State can ensure that these women more easily break away from their aggressors. Furthermore, this study aims to explore the horizontal function of public procurement as a means to combat and mitigate domestic violence. This topic is highly relevant, given that gender-based violence, particularly domestic violence, remains a recurring issue in daily life, in inverse proportion to advancements in other areas. In other words, while various sectors—especially technology—continue to progress, society appears to regress in terms of respect for and protection of women. This research was conducted through a bibliographic review of legal scholarship, the analysis of current news related to the subject, and legislative consultations.